Accidental Activists : Mark Phariss, Vic Holmes, and Their Fight for Marriage Equality in Texas - Collins, David, 1945 June- (Book collections on Project MUSE., 2017)
"Book is a profile of a gay couple who challenged Texas laws against gay marriage. Their case went to the Fifth Circuit Court of Appeals before being superseded by the Supreme Court ruling in Obergefell v. Hodges. Mark Phariss and Vic Holmes live in Plano, Texas. Book contains details on civil rights cases relating to gay rights"--Provided by publisher.